Genomic signal selection analysis reveals genes related to the lambing trait of Hotan sheep - XinKun Wang; Wei Li; QiaoYan Huang; HuiPing Sun; LeXiao Zhu; RuoHuai Gu; Feng Xing (Animal Bioscience)
Objective Lambing in ewes is a complex and crucial aspect of sheep production that directly influences economic viability and production efficiency. In the present study, we analyzed the genomes of single lamb (SLE) and twin lamb (TLE) Hotan sheep to elucidate the genetic mechanisms underlying lamb production in Hotan sheep. Methods In this study, we used genome-wide resequencing to analyze the genomes of Hotan sheep exhibiting SLE and TLE traits. To identify the population genetic structure and linkage disequilibrium associated with SLE and TLE traits, we employed two complementary genome selection signals: the interpopulation genetic differentiation index (FST) and nucleotide diversity. Subsequently, we performed gene annotation and enrichment analyses of the selected regions of the obtained genome. Results Our analysis generated 801 Gb of sequence data, from which 31,864,651 high-quality single nucleotide polymorphic loci were identified. We identified 290 selected regions and 332 genes across the Hotan sheep genome by using two widely adopted selective scanning detection methods (FST statistics and Piratio). Functional annotation and enrichment analysis of these genes identified 13 genes associated with the lambing rate, which were enriched in pathways such as the transforming growth factor-β signaling pathway (BMPR2, ID2, SMAD7, THBS1, and RBX1), renal cell carcinoma (PAK1, ELOC), inositol phosphate metabolism (PLCZ), non-homologous terminal junction (RAD50), ABC transporters (ABCC4), and the NET pathway (H2B, H4, and H2A). Conclusion This study employed selective elimination analysis to identify candidate genes involved in the regulation of lambing trait in Hotan sheep. By investigating the molecular mechanisms underlying lambing rate in Hotan sheep, we developed molecular markers for twin lambing to enhance reproductive performance and promote the conservation and development of outstanding genetic resources in local Xinjiang sheep.